Study of Non-Thermal DC Arc Plasma of CH4/Ar at Atmospheric Pressure Using Optical Emission Spectroscopy and Mass Spectrometry*supported by National Natural Science Foundation of China (Nos. 11035005, 11475174, 50876101) and USTC-NSRL Association Funding (No. KY2090130001). (September 2015) - Liao, Mengran; Wang, Yu; Wu, Hanfeng; Li, Hui; Xia, Weidong
Abstract Non-thermal C/H/Ar plasmas are widely applied to carbonaceous material production and processing. In this work, plasma parameters and gaseous species of the atmospheric non-thermal C/H/Ar plasmas produced by an atmospheric-pressure DC arc discharge generator in CH4/Ar were investigated. The voltage-current characteristics were measured for different CH4/Ar ratios. Optical emission spectroscopy was employed to analyze the electron excitation temperature, gas temperature and electron density under various discharge conditions. The hydrocarbon molecules produced in the CH4/Ar plasmas were detected with photoionization mass spectrometry. The optical spectral results demonstrated that the electron excitation temperature was 0.4-1 eV, the gas temperature was 2800-4200 K and the electron density was in the range of (5-20)×1015 cm−3. The mass spectrum indicated that a variety of unsaturated hydrocarbons (C2H4, C3H6, C6H6, etc.) and several highly unsaturated hydrocarbons (C4H2, C5H6, etc.) were produced in the non-thermal arc plasmas.